Antropologiczny wymiar życia społeczno-gospodarczego w świetle współczesnej polskiej myśli teologiczno-moralnej - Zadroga, Adam (Annales. Etyka w Życiu Gospodarczym, 2008)
The Catholic Church’s Social Teaching dealing with mankind is interested in the person and their way of progressing in the world. As John Paul II stated, Catholic Social Teaching “belongs [...] to the field [...] of theology, particularly moral theology” (SRS 41; CA 55). Polish moralists in the area of social moral theological studies undertake the issue of economic-social life, and in particular its anthropological dimension. Moral reflections from the theological point of view allow for an integral grasping of the involvement of the person in the life of society. The goal of the presented report is to show an integral concept of the person as the fundamental dimension of social-economic life. The principle source of this work is comprised of views presented on the given topic by the nation’s moralists during over a dozen lately held yearly meetings of the Section of Polish Moral Theologians. The contents of the report are divided into three parts: (1) the integrated vision of the person as the principle element of evaluating the social-economic order; (2) threats to the human person in the context of contemporary social-political life and (3) pointing to ways of overcoming these threats.